Finding the remainder!

After spending some mind and time I got the following result:

Given any polynomial f(x)f(x) with degree greater than or equal to 22. And you know that if it is divided by xpx-p the remainder we get is qq. And if it is divide by xqx-q then the remainder is pp, then if you divide it by (xp)(xq)(x-p)(x-q) the remainder you will get will be p+qx\boxed{p+q-x} where xx is a variable and pp and qq are constants and pq\boxed{p≠q}

Proof:

Consider any f(x)f(x), and let consider it's division by xpx-p now it is necessary that degree of f(x)f(x) is greater than or equal to 22 (see why?)

From Division algorithm of polynomials:

f(x)=(xp)g1(x)+qf(x)=(x-p)g_1(x)+q

Where g1(x)g_1(x) is any polynomial

Similarly of we divide it by xqx-q

f(x)=(xq)g2(x)+pf(x)=(x-q)g_2(x)+p

Now if we divide it by (xp)(xq)(x-p)(x-q)

f(x)=(xp)(xq)g3(x)+r(x)f(x)=(x-p)(x-q)g_3(x)+r(x)

From division algorithm of polynomial it follows that degree of r(x)r(x) is smaller than (xp)(xq)(x-p)(x-q) or r(x)=0r(x)=0

As degree of (xp)(xq)(x-p)(x-q) will be 22 therefore the highest possible degree of r(x)r(x) is11. Therefore there exists aa and bb such that r(x)=ax+br(x)=ax+b where it is not necessary that a0a≠0 as r(x)r(x) can also be a constant in that case a=0a=0 and if r(x)=0r(x)=0 then a=0a=0 and b=0b=0.

f(x)=(xp)(xq)g3(x)+(ax+b)f(x)=(x-p)(x-q)g_3(x)+(ax+b)

f(p)=(pp)(pq)g3(p)+(ap+b)=ap+bf(p)=(p-p)(p-q)g_3(p)+(ap+b)=ap+b

andand

f(q)=(qp)(qq)g3(q)+(aq+b)=aq+bf(q)=(q-p)(q-q)g_3(q)+(aq+b)=aq+b

Also as remainder of division of f(x)f(x) and (xp)(x-p) is f(p)f(p) from remainder theorem. Therefore, f(p)=qf(p)=q because both (i.e f(p)f(p) and qq) of them are the remainder of the same division, similarly f(q)=pf(q)=p therefore,

q=ap+bq=ap+b ...(1)

andand

p=aq+bp=aq+b ...(2)

if we subtract the (1) from (2) we get

pq=aqapp-q=aq-ap

pq=a(qp)p-q=a(q-p)

a=1a=-1

putting it in the equation (p=aq+bp=aq+b) we get

p=q+bp=-q+b

b=p+qb=p+q

Therefore the remainder r(x)=ax+b=x+p+q=p+qxr(x)=ax+b=-x+p+q=\boxed{p+q-x}

Note:

  • It is important to note that if p=qp=q then from the equation (pq=a(qp)p-q=a(q-p)) we can't get that a=1a=-1 because in that case pq=qp=0p-q=q-p=0 and as you can't divide anything by 00, therefore pq\boxed{p≠q} as mentioned in the statement above
#Algebra

Note by Zakir Husain
1 year ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

There are no comments in this discussion.

×

Problem Loading...

Note Loading...

Set Loading...